Mengenal Kanker Tiroid Dan Peranan Patologi Anatomi Dalam Menegakkan Diagnosis - Fadillah None None (Surya Edukasi: Jurnal Pengabdian Masyarakat, 2025)
Thyroid cancer is one of the endocrine malignancies with a rising incidence worldwide. Early detection and understanding of risk factors are essential to avoid delayed diagnosis. Anatomical pathology plays a crucial role in establishing the diagnosis through cytology (FNAC), histopathology, and immunohistochemistry. Objective: To evaluate the improvement of community knowledge regarding thyroid cancer, to introduce the role of anatomical pathology in establishing the diagnosis, and to assess participants’ risk factors. Methods: The education program was conducted using interactive lectures and discussions. Pre- and post-education questionnaires were used to assess knowledge level and thyroid cancer risk factors. Results: After the intervention, participants’ knowledge good, with 90% achieving knowledge and 10% showing poor knowledge. High-risk factors were identified in 15% of participants, while 85% were categorized as low risk. Conclusion: Health education on thyroid cancer effectively improved community knowledge. The role of anatomical pathology is essential in establishing the diagnosis of thyroid cancer. Enhancing public understanding is expected to promote early detection and appropriate management.